Surgery in Bilateral Wilms Tumor-A Single-Center Experience - Fernanda Kelly Marques de Souza; Mayara Caroline Amorim Fanelli; Alexandre Alberto Barros Duarte; Maria Teresa de Seixas Alves; Henrique Manoel Lederman; Monica dos Santos Cypriano; Simone de Campos Vieira Abib (MDPI AG, 2023)
The treatment of bilateral Wilms tumors (BWT) involves curing the cancer, preserving long-term renal function, and maintaining a good quality of life. Established methods for achieving these goals include preoperative chemotherapy and nephron-sparing surgery (NSS). This study aimed to evaluate the experience of a single institution in treating patients with BWT. We analyzed cases of BWT treated at the Pediatric Oncology Institute-GRAACC-Federal University of São Paulo over a period of 35 years. Bleeding control was performed with manual compression of the renal parenchyma. Thirty-three patients were included in the study. Thirty cases were synchronous tumors. The mean age at diagnosis was 30.4 months (±22 m) and 66.7% were girls. The median follow-up period was 83 months. Neoadjuvant chemotherapy was the primary approach in most patients (87.9%), with a simultaneous upfront surgical approach performed in 84.8%. Most patients underwent bilateral NSS (70.4%). There were no early complications in this series, but 39.4% had clinical complications. The five-year survival rate was 76%. Therefore, it is clear that the surgical approach to BWT plays a crucial role in achieving good outcomes. However, it is difficult to standardize surgical techniques and technology may have the potential to enhance safety.